2010
DOI: 10.3892/ijo_00000716
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-focused proteomic signatures in HER2-overexpressing breast cancer with a basal-like phenotype: New insights into de novo resistance to trastuzumab (Herceptin)

Abstract: Abstract.Pioneering clinical studies in de novo refractoriness to the anti-HER2 monoclonal antibody trastuzumab have suggested that HER2 gene-amplification can take place also in a basal-like molecular background to generate basal/HER2 + tumors intrinsically resistant to trastuzumab. Here, we first investigated the unique histogenesis of the basal/HER2 + phenotype in breast carcinomas. The presence of basal CK5/CK6 cytokeratin expression in HER2 + tumors revealed a significant overlap in the histological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…IGF1R and IR are frequently expressed at high levels in various malignancies such as breast cancer [ 40 , 41 , 42 ], colorectal cancer [ 43 , 44 ], and NSCLC [ 45 , 46 ]. Dysregulation of IGF1R/IR axis acts as an oncogenic signal in initial tumorigenesis as well as mediating resistance to targeted therapies [ 47 , 48 ]. The IGF2/IGF1R/IR axis mediates adaptive resistance to erlotinib by undergoing an IGF1R/IR phenotypic switch in cholangiocarcinoma [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGF1R and IR are frequently expressed at high levels in various malignancies such as breast cancer [ 40 , 41 , 42 ], colorectal cancer [ 43 , 44 ], and NSCLC [ 45 , 46 ]. Dysregulation of IGF1R/IR axis acts as an oncogenic signal in initial tumorigenesis as well as mediating resistance to targeted therapies [ 47 , 48 ]. The IGF2/IGF1R/IR axis mediates adaptive resistance to erlotinib by undergoing an IGF1R/IR phenotypic switch in cholangiocarcinoma [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and others recently observed that resistance to Trastuzumab leads Her2+ breast cancer cells to display the phenotypes of TNBC through the activation of NF-κB. 10 , 11 TNBC cells are known to harbor constitutive activation of NF-κB, 12 , 13 which is implicated in poor prognosis for TNBC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, little is known about the analysis tools that can be applied to explore changes in the expression of autophagy genes or about the functional importance of putative candidate genes emerging from autophagy-dedicated transcriptome studies. In this context, we first assessed the utility of an autophagy-focused polymerase chain reaction (PCR) array to identify novel autophagy-specific gene biomarkers for intrinsic (primary) resistance to trastuzumab in HER2 gene-amplified breast cancer cells that naturally exhibit bona fide primary resistance to HER-targeted therapies [ 12 , 13 , 17 , 53 - 55 ]. Second, using molecular biology approaches we unambiguously validated whether the autophagy genes differentially expressed in trastuzumab-refractory breast carcinoma cells functionally predicted the primary response to the growth-inhibitory and anti-tumoral effects of trastuzumab.…”
Section: Introductionmentioning
confidence: 99%